Produktivitas dan Pendapatan Sistem Usaha Tani Kedelai dengan Berbagai Sistem Jajar Legowo - Mardian, Irma; Hipi, Awaludin; Widyastuti, Eka (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
The interest of Indonesian farmers to grow soybean is relatively low because the price of soybean is not competitive and tend to be low. Therefore there is a need to increase the interest of farmers to grow soybean. One of them by increasing crop productivity through the use of the right planting system. This study aims to test the various doble row planting systems that is able to provide the best productivity for soybean and increase farmer's income. The research was conducted by demo farm method on 3 ha of farmer land in Ntuwu Lamba farmer group of Sambinae urban village of Bima. The experiment was design based on a randomized block design where there were 3 sowing distance treatments that were planted at 40 x 10-15 cm, double row system 60-30 cm x 10 cm, and double row planting system 40-20 x 10 cm. The result of the study showed that the double row planting system of 60-30 x 10 cm gave the highest yield on both agronomic and yield parameters. Financial analysis shows that jajar legowo of 60-30 x 10 cm resulting in the highest profit of Rp. 10.058.000/ha and R/C ratio of 2.47 and B/C 1.47.